Spectral and temporal acoustic differences between English and Dutch vowels - Georgiou, Georgios P. (Journal of Monolingual and Bilingual Speech, 2024)
This study aims to compare the acoustic characteristics of English and Dutch vowels and to model the perception of Dutch vowels by English speakers on the basis of crosslinguistic acoustic similarity. The first three formant frequencies and the duration of vowels were extracted from the output of 20 native English and 20 native Dutch speakers. A linear discriminant analysis (LDA) algorithm was trained on the productions of English speakers and the Dutch productions were later supplied to the model to provide a predicted proportion of how each nonnative vowel would be classified in terms of the speakers’ L1 categories. The results of LDA demonstrated that all but one Dutch vowel were classified as above-chance responses in terms of two or more English categories. Due to the large and complex vowel system of English, completely overlapping contrasts were absent, while there was a large number of partially overlapping contrasts, which are predicted to exhibit moderate-to-good discrimination. The results of crosslinguistic acoustic similarity are largely consistent with those involving other English listeners of Dutch, potentially highlighting the importance of acoustic cues in estimating listeners’ speech perception patterns.